Digital Lifestyle and Food Waste Behavior: The Role of Camera Eats First in Cafes and Restaurants in Batam City, Indonesia - Saputra, Eryd; Alhamdi, Rezki (Industrial and Domestic Waste Management, 2025)
Camera eat first referred to the habit of photographing food before consumption for sharing on social media. This phenomenon drove shifts in consumer behavior, potentially leading to increased food waste. The objective of this study was to analyze the influence of attitude, emotion, and perceived behavioral control on food waste behavior, with camera eat first included as a mediating variable. A quantitative approach was employed, involving a sample of 340 respondents who were visitors to cafés and restaurants in the Harbour Bay area of Batam. Data were collected using a five-point Likert scale questionnaire and analyzed through Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS software, as well as Fuzzy-Set Qualitative Comparative Analysis (fsQCA). The findings revealed that emotions and perceived behavioral control exerted a positive and significant effect on food waste behavior, whereas attitude and camera eat first did not show significant influence. Furthermore, camera eat first was not confirmed as a mediator in the relationships among the studied variables. Complementary results from fsQCA highlighted that the combination of attitude, emotion, and perceived behavioral control constituted the most consistent configuration in explaining food waste behavior. Overall, the study concluded that food waste behavior was more strongly shaped by internal psychological factors than by digital lifestyle trends. Consequently, strategies to reduce food waste should prioritize strengthening self-control, enhancing emotional awareness, and promoting responsible consumption practices, while also accounting for the dynamics of social media engagement in contemporary society.